Specific Magnetic Isolation of E6 HPV16 Modified Magnetizable Particles Coupled with PCR and Electrochemical Detection - Jimenez Jimenez, Ana Maria; Ruttkay-Nedecký, Branislav; Dostálová, Simona; Krejčová, Ludmila; Richtera, Lukáš; Adam, Vojtěch; Michálek, Petr (MDPI, 2016)
The majority of carcinomas that were developed due to the infection with human papillomavirus (HPV) are caused by high-risk HPV types, HPV16 and HPV18. These HPV types contain the E6 and E7 oncogenes, so the fast detection of these oncogenes is an important point to avoid the development of cancer. Many different HPV tests are available to detect the presence of HPV in biological samples. The aim of this study was to design a fast and low cost method for HPV identification employing magnetic isolation, polymerase chain reaction (PCR) and electrochemical detection. These assays were developed to detect the interactions between E6-HPV16 oncogene and magnetizable particles (MPs) using commercial Dynabeads M-280 Streptavidin particles and laboratory-synthesized “homemade” particles called MANs (MAN-37, MAN-127 and MAN-164). The yields of PCR amplification of E6-HPV16 oncogene bound on the particles and after the elution from the particles were compared. A highest yield of E6-HPV16 DNA isolation was obtained with both MPs particles commercial M-280 Streptavidin and MAN-37 due to reducing of the interferents compared with the standard PCR method. A biosensor employing the isolation of E6-HPV16 oncogene with MPs particles followed by its electrochemical detection can be a very effective technique for HPV identification, providing simple, sensitive and cost-effective analysis.

The majority of carcinomas that were developed due to the infection with human papillomavirus (HPV) are caused by high-risk HPV types, HPV16 and HPV18. These HPV types contain the E6 and E7 oncogenes, so the fast detection of these oncogenes is an important point to avoid the development of cancer. Many different HPV tests are available to detect the presence of HPV in biological samples. The aim of this study was to design a fast and low cost method for HPV identification employing magnetic isolation, polymerase chain reaction (PCR) and electrochemical detection. These assays were developed to detect the interactions between E6-HPV16 oncogene and magnetizable particles (MPs) using commercial Dynabeads M-280 Streptavidin particles and laboratory-synthesized “homemade” particles called MANs (MAN-37, MAN-127 and MAN-164). The yields of PCR amplification of E6-HPV16 oncogene bound on the particles and after the elution from the particles were compared. A highest yield of E6-HPV16 DNA isolation was obtained with both MPs particles commercial M-280 Streptavidin and MAN-37 due to reducing of the interferents compared with the standard PCR method. A biosensor employing the isolation of E6-HPV16 oncogene with MPs particles followed by its electrochemical detection can be a very effective technique for HPV identification, providing simple, sensitive and cost-effective analysis.
Specific Magnetic Isolation of E6 HPV16 Modified Magnetizable Particles Coupled with PCR and Electrochemical Detection
Keywords: electrochemistry; human papillomavirus; magnetic isolation; nucleic acid detection; magnetizable particles; PCR; electrochemistry; human papillomavirus; magnetic isolation; nucleic acid detection; magnetizable particles; PCR